POTENCY WATER STEW OF AVERRHOA BILIMBI L FOR ANTIHYPERTENSIVE - indah - lestari; Anissa Melania; Budi Prasetyo (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Hypertension is often referred to as a